Exploring the Nutritional, Phytochemical, and Antibacterial Properties of Green Banana Pulp and Peel: A Comparative Analysis - Susmita Chowdhury; Bappa Aich; Arpita Chowdhury; Monsur Ahmad (Knowledge Dynamics, 2025)
Background: Bananas, esteemed for their nutritional benefits and historical therapeutic use, are a favored fruit among consumers. Paradoxically, the banana peel, a significant by-product of the banana processing industry, is often disregarded and treated as waste. Nonetheless, banana peels represent an overlooked source of nourishment and adaptability. This study aimed to conduct a thorough evaluation of the nutritional composition, phytochemical properties, and bioactivity of green banana pulp and peel extracts. Methods: Banana pulp and peel were subjected to oven drying at a regulated temperature, and proximate analysis was conducted in accordance with AOAC methodologies. The analysis of bioactive components and antioxidant capability was conducted using a UV-visible spectrophotometer. High Performance Liquid Chromatography (HPLC) was utilized to identify active constituents such as phytochemicals in the extract. The disc diffusion method was utilized to assess the efficacy of the extracts against Escherichia coli and Staphylococcus aureus. Results: The banana peel powder had higher levels of crude protein (7.18±0.02%), crude fat (8.56±0.04%), crude fiber (26.77±0.096%), and ash (10.12±0.0106%). In contrast, banana pulp powder had higher moisture (6.09 ± 0.06%) and carbohydrate (81.76 ± 0.065%) content. The total flavonoid content in banana peel (226.22 mg QE/100g) was higher than that of banana pulp (58.21 mg QE/100g), and banana pulp had the highest total polyphenol content (24.06 mg GAE/100g). Both extracts contained essential tannins, and flavonoids, according to phytochemical screening. Also, banana pulp and peel extracts showed antibacterial activity against S. aureus and E. coli. Conclusion: This study emphasizes the enhanced nutritional profile of green banana peel relative to pulp, alongside its promising phytochemical and bioactive properties. Thus, banana pulp and peel powder may serve as valuable resources with various applications, fostering healthier diets, sustainable agriculture, and environmentally friendly innovations.